Pengaruh Media Kantong Bilangan Animasi Terhadap Kemampuan Berhitung Anak Paud Kasih Ibu Subo - Yunita Marlina Salang; I Made Suarjana; Putu Rahayu Ujianti (Universitas Pendidikan Ganesha, 2022)
This development research is aimed at improving the learning outcomes of number recognition in Ibu Subo's Early Childhood Education with the help of number bag media. By using development research design, this research involves several subjects, namely (1). validation subjects consisting of media experts, material experts and practitioners, (2) the subject of the trial, namely small group trials and large group trials, there are two types of data, namely qualitative and quantitative. Data collection techniques used in this study are observation techniques, and questionnaires (questionnaires). The instrument used in this study was a questionnaire. The analysis shows the contribution obtained from the use of pocket animation media on the learning outcomes of recognizing numbers at the Kasih Ibu Subo PAUD. These results are proven by the validity of a very good score from the experts with the validity of media experts getting a score of 91%, the results of the validity of material experts getting a score of 95%, the results practitioner validity obtained a score of 90.5%. So the application of this animated number bag media is said to be